Argument Structure in an Austronesian Language: The Case of Batak Toba of Aek Kanopan Dialect - Asridayani Asridayani; I Ketut Artawa; Made Sri Satyawati; Ketut Widya Purnawati (Randwick International of Social Science Journal, 2026)
This study examines the argument structure of Batak Toba, focusing on Aek Kanopan dialect, as part of a broader investigation into Austronesian grammatical typology. The main objective is to describe how arguments are structured, realized, and aligned within clauses, and to identify the typological characteristics underlying these patterns. Employing a descriptive qualitative approach, the data were collected through elicitation, participant observation, and interviews with native speakers. The analysis reveals that Batak Toba Aek Kanopan Dialect (BBTAK) exhibits a predominantly accusative alignment, where the single argument of intransitive clauses (S) is treated similarly to the agent of transitive clauses (A), while the patient (P) is marked differently. The study also shows that core arguments in BBTAK are not restricted to nominal phrases, but may also be realized as clauses or propositions, reflecting structural flexibility. These findings contribute to the typological description of Batak Toba and provide empirical evidence for understanding argument structure in Austronesian languages.